(3CReI GdejGg aj GdhWf GdYQHj (B/s - (3SYjO, QTOjs; (3GdWhjd, SYO s ((3GdbGgQI(B: s (3OGQ GdCejf ddfTQ hGdJhRjY(B, s, 2004)
(3CReI GdejGg aj GdTQb GdChSW,TM GdejGg hGdUQGY GdYQHj GdGSQGFjdj,GdeGA aj efWbI GdTGe,efGbTGJ GdLdSI GdChdi,GbJQGM dRjGOI eSGMI GdCQV HfaS cejGJ ejGg GdQj,CReI GdejGg aj hGOj Gdfjd,efGbTGJ GdLdSI GdKGfjI,eSJbHd GdESJaGOI ef ejGg Gdfjd,VHW eGA Gdfjd,GSJNOGe Ohd MhV Gdfjd dejGgg,GJaGbjI VHW hJhRjY ejGg Gdfjd Hjf GdOhd GdfjdjIs
(3HHdjhZQGajG(B: (3U(B.107 (3bGFeI eWHhYGJ eQcR GdHMhK GdYQHjI U(B.115s
Keywords: (3GdejGgs; (3GdhWf GdYQHjs